2013
DOI: 10.1002/aenm.201300275
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol OT/Water System Coupled with Triiodide/Iodide (I3/I) Redox Electrolytes for Highly Efficient Dye‐Sensitized Solar Cells

Abstract: Dye‐sensitized solar cells (DSCs) are considered to be a promising alternative to Si‐based photovoltaic cells. The electrolyte of the DSC primarily uses triiodide/iodide (I3−/I−) as a redox couple. Therefore, it is essential to understand the regeneration and recombination kinetics of the I3−/I− redox couples in the device. In this context, controlling the total and local concentrations of the I3−/I− redox couples is an important parameter that can influence the DSC performance. Here, we propose that the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Compared with organic solvents, water is earth abundant, inexpensive and non-toxic which could be a good candidate to replace organic solvents for liquid electrolyte DSSCs. 8,9 Recently, 100% water based DSSCs have been studied by several groups. [10][11][12][13][14] For example, water based liquid electrolyte DSSCs with an efficiency of 2.4% were achieved under 1 sun light illumination using the I À /I 3 À redox couple.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with organic solvents, water is earth abundant, inexpensive and non-toxic which could be a good candidate to replace organic solvents for liquid electrolyte DSSCs. 8,9 Recently, 100% water based DSSCs have been studied by several groups. [10][11][12][13][14] For example, water based liquid electrolyte DSSCs with an efficiency of 2.4% were achieved under 1 sun light illumination using the I À /I 3 À redox couple.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies conicted with the above and suggested that the introduction of an anionic surfactant, sodium bis(2-ethylhexyl) sulfosuccinate (AOT), increased the hydrophobicity of the dye-coated TiO 2 lm by preventing water from approaching the dye and reducing the recombination rate. 8 So what is the effect of surfactants on water based DSSCs? The reported ndings pushed us to analyze the interface properties of TiO 2 lms and surfactant doped water electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Our best solar energy to electricity conversion efficiencies (η ~ 0.3%) were comparable to those determined in other published studies (η ~ 0.5% 10 ; η ~ 0.8% 8 ). Conversion efficiencies obtained with LHCII-based bio-dyes were, however, far lower than those reported for Ruthenium-based organic dyes (η in the range of 3–11%) 17,18 , frequently used in conjunction with TiO 2 photoanodes.…”
Section: Resultsmentioning
confidence: 60%
“…4b and Table 1). h cc can be estimated by the two values determined from the above IMPS and IMVS by adopting the following equation: [40][41][42]…”
Section: Resultsmentioning
confidence: 99%